1999
DOI: 10.1046/j.1439-0523.1999.118001075.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of two new cytoplasmic male‐sterile lines in Brassica juncea through wide hybridization

Abstract: Two new cytoplasmic male‐sterile (CMS) lines have been developed in Brassica juncea using the bridgecross hybrids (Diplotaxis erucoides×Brassica campestris)×B. juncea and (Diplotaxis berthautii×B. campestris)×B. juncea. These were backcrossed ×ve times with pollen of B. juncea. The CMS line (D. erucoides) B. juncea segregated into tall and short true breeding types; both resembled the cultivar B. juncea in vegetative and floral morphology and in cytology, except for a greater number of secondary branches and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…6C). These structures resemble the thirdwhorl filamentous organs observed in several Arabidopsis mutants including ufo (Wilkinson and Haughn, 1995), afo (Kumaran et al, 1999), and fil (Sawa et al, 1999), and have also been observed in species hybrids (Michaelis, 1954;Malik et al, 1999;Matsuzuwa et al, 1999).…”
Section: Variation For Developmental Traits and Chromosome Assortmentmentioning
confidence: 67%
“…6C). These structures resemble the thirdwhorl filamentous organs observed in several Arabidopsis mutants including ufo (Wilkinson and Haughn, 1995), afo (Kumaran et al, 1999), and fil (Sawa et al, 1999), and have also been observed in species hybrids (Michaelis, 1954;Malik et al, 1999;Matsuzuwa et al, 1999).…”
Section: Variation For Developmental Traits and Chromosome Assortmentmentioning
confidence: 67%
“…Owing to this, reports describing vegetative alterations in CMS plants are not common. Nevertheless, reduced plant height and retarded vegetative growth have been reported in plants from other alloplasmic CMS systems such as B. juncea (Malik et al, 1999), N. tabacum (+Hyoscyamus niger) cybrids (Zubko et al, 2001), alloplasmic N. tabacum lines (I Farbos, unpublished results), and T. aestivum (Ikeda and Tsunewaki, 1996). Of relevance is that two N. sylvestris CMS plants characterized by large mtDNA deletions leading to the absence of the NAD7 subunit of complex I, developed slowly.…”
Section: Discussionmentioning
confidence: 93%
“…Cybrids from e.g. Nicotiana (Aviv and Galun 1986;De Paepe et al 1990;Gutierres et al 1997) and Brassica juncea (Malik et al 1999), resembled the fertile type in most features, but the male-sterile lines were usually shorter and retarded in growth. These alterations were stably transmitted through sexual generations.…”
Section: Discussionmentioning
confidence: 98%
“…Although reports about vegetative development are less frequent, mtDNA rearrangements associated with reduced growth and abnormal vegetative development have been reported in maize (Newton and Coe 1986), in tobacco (Bonnett et al 1993) and in wheat (Ikeda and Tsuunewaki 1996). Furthermore, Kirti et al (1995) and Malik et al (1999) found variation in flowering time in Brassica juncea combined with cytoplasms from other Brassica species.…”
Section: Introductionmentioning
confidence: 96%